Endophytic Trichoderma virens triggers induced systemic resistance in oil palm seedlings - Md Paudzai, Farah Amira (2018)
Basal stem rot disease caused by Ganoderma spp. is a crucial disease of oil palm (Elaeis guineensis Jacq.) and a major economic concern in Southeast Asian countries. The disease causes death of oil palm by slowly rotting the trunk base of oil palm. Fungicide or herbicide has long been the temporary solution for the disease control, however, planters prefer for natural solution using biological control agent such as endophytic microorganisms. Trichoderma is a well-known biological control agent (BCA) for plant disease and has shown to be effective against basal stem rot (BSR) infection. Trichoderma possesses control mechanism through mycoparatism, antibiosis, and also trigger induced systemic resistance (ISR) in plant. Trichoderma produces compounds and cell-wall degrading enzymes during the colonization of plant roots, thus, limiting the growth of pathogenic fungi. Thus, this study attempts to investigate endophytic Trichoderma ability as an antagonistic biocontrol against Ganoderma boninense and its ability to prime the immune system of the host through ISR. Two potential endophytic Trichoderma isolates 7b and 159c were identified using universal primer pairs TW81 and AB28. The amplification of internal transcribed (ITS) region produced a fragment 600bp. Sequence analysis of 7b and 159c isolates revealed that the isolates showed 99 % percent identical to Trichoderma virens strains available in Genbank database. Phylogenetic analysis showed that T. virens isolate7b and 159c are grouped in same clade with other T. virens and Hypocrea virens. The potential of both T. virens isolates 7b and 159c to be used as BCA were assessed through in vitro assays by percentage inhibition of radial growth (PIRG) and potential in dual culture (PIRG: 65.33% ± 1.42 and 67.20% ± 2.19) and poison agar assay (PIRG: 91.06% ± 9.63 and 58.82% ± 8.64). Observation using scanning electron microscope (SEM) detected severe mycelia deformation such as shriveling, clumping, and shrinking of Ganoderma boninese hyphae in the presence of T. virens isolate 7b and 159c. The zone of interaction between the pathogen and T. virens isolates 7b and 159c detected mycoparatism activity to which breaking and coiling of BSR pathogen by T,virens was observed. Oil palm seedlings inoculated with combination of T. virens isolates 7b and 159c have increased in vegetative parameters such as height, girth, frond count and chlorophyll content. However, disease suppression was significantly the highest in seedlings treated with T. virens isolate 159c having the disease severity of 16.98% when compared to other treatments. Seedlings inoculated with T. virens isolate 159c significantly reduced the disease development measured as the area under disease progression curve (AUDPC) with disease reduction of 64.04% (P<0.05). External and internal symptom of BSR development in oil palm seedlings were correlated each other. Production of peroxidase, polyphenol oxidase, phenylalanine lyase, superoxide dismutase, chitinase, and β-1,3-glucanase were measured using enzymatic assay from leaf tissue upon inoculation of T. virens isolates 7b and 159c. Treatment of T. virens enhanced the levels of plant defense-related enzymes in oil palm seedlings. This study showed that the inoculation of T. virens isolates 7b and 159c triggered the induced systemic resistance in oil palm seedlings through induction of defense enzymes. Application of endophytic T. virens to oil palm seedlings is effective to control the development of BSR disease in oil palm.